Empowerment of the Aisyiyah Women's Community in Jaten District for Achieving Family Resilience and Addressing Climate Change - Khoiriyah, Siti; Hidayat, Agung; Arif, Akbarudin; Saptaningtyas, Haryani (Prospect Publishing, 2025)
Climate change is a global challenge affecting various aspects of life, including family resilience. Women’s communities, particularly members of Aisyiyah in Jaten District, have significant potential to lead family resilience efforts in addressing climate change. The impacts of climate change, such as extreme temperature rises and unstable weather patterns, affect the agricultural sector, a primary source of livelihood. Women, who are often responsible for household food production, face additional burdens due to food and water shortages. Therefore, a community empowerment program is essential, focusing on education about climate change, adaptation, and mitigation, alongside training in environmentally-based economic activities. The activities include composting, liquid fertilizer production, and crafting handicrafts from economically valuable waste. The program aims to enhance community members' understanding of climate change impacts, improve mitigation skills, and promote community welfare through household waste management. The introduction of simple technologies such as composters, organic liquid fertilizers, and accessories from organic waste received positive responses from the community, providing education and motivation for direct waste management practices.